Quad-Active-Bridge Resonant-Type Single-Stage Three-Phase AC-DC Converter: Modulation and Control for V2G Applications - Sal Rosas, D.; Chavez, D.; Tafur, J. (Institute of Electrical and Electronics Engineers, 2025)
The single-stage (SS) ac–dc converter is a promising solution for bidirectional electric vehicle chargers (BEVCs) due to its smaller volume, higher efficiency, and durability compared with the two-stage ac–dc converter. Nevertheless, typically SS ac–dc structures implement highly complex modulation schemes because most of them use bipolar voltage switches. In this article, a novel modulation and control strategy is introduced for the SS quad-active-bridge resonant-type ac–dc converter, which only uses unipolar voltage switches. In the proposed modulation, grid voltages are modulated by duty ratio (DR), whereas the dc source voltage is modulated by phase-shift (PS) and DR. The PS angle takes a constant value according to grid currents amplitude. Moreover, the DR angles, used to modulate grid voltages, control the sinusoidal shape of grid currents according to proportional-integral-resonant controllers cascaded to a second-order low-pass filters and an active damping. Whereas, the DR angle, used to modulate the dc source voltage, is applied to reduce the high-frequency current, in case of reactive power transfer to the grid. Experimental results from a 1.5 kW prototype show high efficiency (96.4%), bidirectional active-reactive power transfer capability, and low harmonic distortion in the grid currents (1.1%), making it an ideal alternative for BEVCs.
Keywords: Half bridge; Electrical engineering; Modulation (music); Single phase; Electronic engineering; Control theory (sociology); Physics; Materials science; Topology (electrical circuits); Capacitor; Computer science; Engineering; Control (management); Voltage; Acoustics; https://purl.org/pe-repo/ocde/ford#2.02.04